The Chanca Kingdom - Espinoza Soriano, Waldemar (2018)
Ethnicity of the most remarkable of the old Peru. It appeared after the fall of the Wari empire. Soon after long migrations settled in the territory of Andahuaylas in the central Andes.There he ordered his lordship or apocuracazgo between the eleventh and twelfth centuries. Divided in Anansaya and Urinsaya, he acquired so much power that he thought of annexing other ethnic groups. It failed in its attempt to be defeated by the Incas of Cusco in the decade of 1430. It continued like Wamani of the Tahuantinsuyo and soon like corregimiento of the virreinato. It persists until today with the category of province of the department and Apurimac region.